UNDERSTANDING OF DOING RESEARCH AND ITS GUIDELINES TO DO A GOOD RESEARCH - Salmon Pandarangga (Universitas Kristen Wira Wacana Sumba, 2021)
Research has well-known as an effective tool to reveal the nature of phenomena and events that occurs around human beings and their environment. A group of experts or well-known as researchers with their curiosity manner always lead them to question why a certain kind of phenomena or event occurs around human beings. For example, researchers curiously question why some students bully other students or why these students are bullied at schools. These questions lead these researchers to investigate these bullying phenomena at schools. It seems that research is about to investigate a certain issue in order to find the answer and the truth as well and why the issue emerged. However, this kind of explanation about research is not yet clear. It is thus very important to have a good understanding of doing a research such as assumptions, paradigms, ideology and methodsof research itself. This article discusses the understanding of doing research and its guidelines to do a good research.Keywords: research assumptions, paradigm, ideology, methods